Cardiovascular safety and lower severe hypoglycaemia of insulin degludec versus insulin glargine U100 in patients with type 2 diabetes aged 65 years or older: Results from DEVOTE (DEVOTE 7). Issue 7 (15th April 2019) - Pratley, Richard E.; Emerson, Scott S.; Franek, Edward; Gilbert, Matthew P.; Marso, Steven P.; McGuire, Darren K.; Pieber, Thomas R.; Zinman, Bernard; Hansen, Charlotte T.; Hansen, Melissa V.; Mark, Thomas; Moses, Alan C.; et al.
Abstract : Aims: The aim of this study was to describe the risks of cardiovascular (CV) events and severe hypoglycaemia with insulin degludec (degludec) vs insulin glargine 100 units/mL (glargine U100) in patients with type 2 diabetes (T2D) aged 65 years or older. Materials and methods: A total of 7637 patients in the DEVOTE trial, a treat‐to‐target, randomized, double‐blind trial evaluating the CV safety of degludec vs glargine U100, were divided into three age groups (50‐64 years, n = 3682; 65‐74 years, n = 3136; ≥75 years, n = 819). Outcomes by overall age group and randomized treatment differences were analysed for major adverse cardiovascular events (MACE), all‐cause mortality, severe hypoglycaemia and serious adverse events (SAEs). Results: Patients with increasing age had higher risks of CV death, all‐cause mortality and SAEs, and there were non‐significant trends towards higher risks of MACE and severe hypoglycaemia. Treatment effects on the risk of MACE, all‐cause mortality, severe hypoglycaemia and SAEs were consistent across age groups, based on the non‐significant interactions between treatment and age with regard to these outcomes. Conclusions: There were higher risks of CV death, all‐cause mortality and SAEs, and trends towards higher risks of MACE and severe hypoglycaemia with increasing age after adjusting for baseline differences. The effects across age groups of degludec vs glargine U100 on MACE, all‐cause mortality and severe hypoglycaemia were comparable, suggesting that the risk of MACE, as well as all‐cause mortality, is similar and the risk of severe hypoglycaemia is lower with degludec regardless of age. Evidence is conclusive only until 74 years of age.